Comparing cost-optimal and net-zero energy targets in building retrofit. Issue 2 (17th February 2016) - Ferreira, Marco; Almeida, Manuela; Rodrigues, Ana; Silva, Sandra Monteiro
Abstract : The recast of the European Union's Energy Performance of Buildings Directive introduced the concept of nearly zero-energy buildings, requiring its adoption from 2021 by all new buildings and existing ones submitted to major renovations. European Union member states must also ensure minimum energy requirements for buildings in order to achieve cost-optimal levels during their life cycle. Cost optimality and nearly zero-energy buildings are important concepts in European Union energy policies. These concepts are related, but one is more focused on costs, while the other is more concerned with low energy consumption and on site-renewable energy harvesting. If these approaches result in major differences in the selection of the best package of retrofit measures, then the transition from the cost-optimal concept to nearly zero-energy buildings might be problematic. To assess the most cost-effective solutions to achieve net-zero, a building in Porto, Portugal, was analysed. This determined not only the most cost-effective retrofit solutions but also compared these net-zero solutions with those resulting from the cost-optimal calculation. Both approaches lead to similar results, indicating that the transition between 'cost optimality' to 'nearly zero-energy buildings' could occur in Portugal.